Effect of T-scan Occlusal Analysis and Adjustment Versus Articulating Paper on Stresses Transmitted to Single Mandibular Implant Supported Prosthesis - Saud, Mohammed; Alafandy, Mahmoud; Osama , Ahmed Mohamed; El-Sadat, Omar Abbas (Open Access Macedonian Journal of Medical Sciences, 2023)
AIM: The study aimed to compare two different methods for occlusal analysis and adjustment of implant-supported prostheses (computerized T-scan and articulating papers) regarding the stresses transmitted to the implants. MATERIALS AND METHODS: Seven patients with completely edentulous mandible opposing dentate maxilla have been selected and four implants have been inserted. Two identical mandibular zirconia implant supported prostheses have been constructed for each patient. Occlusal analysis and adjustments have been done using T-scan for one prosthesis and using articulating papers for the other prosthesis. Two identical acrylic casts for the mandibular arch (with four implant analogs on each cast) have been constructed for each patient. The prostheses on their acrylic casts were applied to cyclic loading using chewing simulator of 250,000 cycle (1 year loading). Strain gauges have been installed mesial and distal to each implant (28 implants of T-scan group and 28 implants of articulating paper group) and strain gauge analysis was conducted using the universal testing machine upon the application of bilateral and unilateral load after cyclic loading. Data were collected, tabulated, and statistically analyzed. RESULTS: Higher micro strain values were found around implants among articulating paper group than T-scan group and that difference was statistically insignificant under bilateral loading and statistically significant under unilateral loading. CONCLUSION: T-scan allows better occlusal stresses distribution as it brings additional information regarding force intensity and occlusal timing resulting in less stresses transmitted around implants.